1988
DOI: 10.3109/01050398809070694
|View full text |Cite
|
Sign up to set email alerts
|

The Site of the Lesion Causing Deafness in Multiple Sclerosis

Abstract: A patient with multiple sclerosis who developed sequential hearing loss, first on the right, with recovery is discussed. Magnetic resonance imaging demonstrated lesions in the VIII nerve root entry zones which were thought to be responsible for the hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…The most common type of hearing loss (after normal hearing) for the group of subjects with MS and for the group of control subjects without MS was sensorineural hearing loss. This is the most common type of hearing loss typically reported in articles of both individuals with and without MS. Additionally, this type of hearing loss is consistent with the disease process of MS and prior investigations have suggested that sensorineural hearing loss in individuals with MS is due to swelling and/or scarring in the lower portions of the central auditory pathways or in the cochlear nerve [24,26,28,30,[33][34][37][38] …”
Section: Discussionmentioning
confidence: 48%
“…The most common type of hearing loss (after normal hearing) for the group of subjects with MS and for the group of control subjects without MS was sensorineural hearing loss. This is the most common type of hearing loss typically reported in articles of both individuals with and without MS. Additionally, this type of hearing loss is consistent with the disease process of MS and prior investigations have suggested that sensorineural hearing loss in individuals with MS is due to swelling and/or scarring in the lower portions of the central auditory pathways or in the cochlear nerve [24,26,28,30,[33][34][37][38] …”
Section: Discussionmentioning
confidence: 48%
“…Jacobs et al [ 13] and Barratt et al [14] have reported that the lesion did not change over time. Johnson et al [15] Ormerod et al [16] and Costantino et al [17] have reported about the changes of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Barratt et al [14] have hypothesized that demyelinated fibers could transmit impulses, despite the failure of those fibers to transmit impulses at normal velocities, which accounts for the ABR abnormalities. Wc think that the explanation for the difference between recoverable neurological signs and the remaining signs is of importance in the pathophysiological mechanism of MS.…”
Section: Discussionmentioning
confidence: 99%
“…However, deafness from intrinsic brainstem disease is very uncommon because hearing is represented bilaterally in the ascending pathways (lateral lemnisci). The more usual explanation for permanent bilateral deafness rarely accompanying acute demyelinating encephalomyelitis, is either associated peripheral labyrinthine damage, for example, zoster involvement of the cochlear nerves (“Ramsay Hunt syndrome plus”)5 or bilateral cochlear nerve root damage at the entry zones 6…”
Section: What Was Goya’s Disease?mentioning
confidence: 99%